SEARCH FOR UNIVERSAL COMBINED ANTIHYPERTENSIVE THERAPY WITHIN LIMITED DATA ON THE COMPARATIVE EFFICACY OF ANTIHYPERTENSIVE AGENTS - S. R. Gilyarevskiy (Столичная издательская компания, 2015)
Modern approaches to the choice of antihypertensive drugs are considered. Definitions of the "universal" combined antihypertensive therapy that can be effective in most hypertensive patients, regardless of their individual characteristics are discussed. Results of the most significant clinical trials evaluating the efficacy of combined antihypertensive therapy and the relevant provisions of up-to-date clinical recommendations are given as arguments.